Measurement of Digital Literacy Among Students at SMAN 1 Kesesi, Pekalongan Residence - Fauzi, M Imam; Al Muhdhar, Mimien Henie Irawati; Susanto, Hendra (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Digital literacy is important for every student to have. Digital literacy needs to be trained and learned to form a young generation that is digitally literate so that they are ready to participate in the digital community with confidence in communicating, sharing and distributing knowledge in a useful and efficient way, provides readiness to adapt successfully to a changing work environment and increasing self-control as a solution to the spread of false information that continues to repeat itself and is increasing in number. This research aims to measure students' digital literacy at SMAN 1 Kesesi. The methods used were filling out questionnaires and conducting interviews. Seventy-six eleventh-grade students of SMAN 1 Kesesi, Pekalongan Residence, Central Java, Indonesia, and two biology teachers were selected as the research sample in this study. The research results showed the following aspects: Firstly, the student's digital literacy questionnaire is 71%, which is classified as moderate in digital literacy indicators including finding, using sources, selecting, evaluating, considering sources, message effects, and using data to produce work; secondly, some of the things that teachers do to train these two skills are by inviting students to search for information via Google/search engines and video searches to support the teacher's explanations and using Canva to make some presentation. Unfortunately, teachers do not train them on how to search using appropriate keywords and trusted sources. Finally, teachers must be more active and innovative in maximizing the wise use of digital media to improve students' digital literacy.